Error, consistency and triviality. (16th June 2021) - Tiefensee, Christine; Wheeler, Gregory
Abstract: In this paper, we present a new semantic challenge to the moral error theory. Its first component calls upon moral error theorists to deliver a deontic semantics that is consistent with the error‐theoretic denial of moral truths by returning the truth‐value false to all moral deontic sentences. We call this the 'consistency challenge' to the moral error theory. Its second component demands that error theorists explain in which way moral deontic assertions can be seen to differ in meaning despite necessarily sharing the same intension. We call this the 'triviality challenge' to the moral error theory. Error theorists can either meet the consistency challenge or the triviality challenge, we argue, but are hard pressed to meet both.